Perspektif Hukum Terhadap Pembatalan Pembayaran Konsumen dalam E-Commerce Menggunakan Cash On Delivery (COD) - Sulis Tyaningsih; Rina Arum Prastyanti (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
E-commerce in Indonesia has grown rapidly, facilitating transactions between consumers and businesses. One popular payment method is Cash on Delivery (COD), where the buyer pays in cash upon receipt of the goods. However, this method often disadvantages businesses, especially when consumers cancel orders or cannot be reached. This study uses a normative juridical method to discuss the e-commerce payment system and legal protection for businesses against payment cancellation by consumers in the COD system. Factors causing losses for businesses in the practice of COD payments include buyers with bad intentions, non-payment according to agreement, and damage to goods. The lack of legal regulation regarding protection for businesses in the COD payment system causes losses for businesses in running their operations. This study aims to explain the payment system between consumers and businesses in e-commerce transactions and analyze protection for businesses in the event of consumer e-commerce transaction cancellations in the cash on delivery system..Perspektif Hukum Terhadap Pembatalan Pembayaran Konsumen dalam E-Commerce Menggunakan Cash On Delivery (COD)